Acute kidney injury and acute-on-chronic liver failure classifications in prognosis assessment of patients with acute decompensation of cirrhosis. Issue 10 (13th October 2014) - Angeli, Paolo; Rodríguez, Ezequiel; Piano, Salvatore; Ariza, Xavier; Morando, Filippo; Solà, Elsa; Romano, Antonietta; García, Elisabet; Pavesi, Marco; Risso, Alessandro; Gerbes, Alexander; Willars, Chris; et al.
Abstract : Objective: Prognostic stratification of patients with cirrhosis is common clinical practice. This study compares the prognostic accuracy (28-day and 90-day transplant-free mortality) of the acute-on-chronic liver failure (ACLF) classification (no ACLF, ACLF grades 1, 2 and 3) with that of acute kidney injury (AKI) classification (no AKI, AKI stages 1, 2 and 3). Design: The study was performed in 510 patients with an acute decompensation of cirrhosis previously included in the European Association for the Study of the Liver–Chronic Liver Failure consortium CANONIC study. ACLF was evaluated at enrolment and 48 h after enrolment, and AKI was evaluated at 48 h according to Acute Kidney Injury Network criteria. Results: 240 patients (47.1%) met the criteria of ACLF at enrolment, while 98 patients (19.2%) developed AKI. The presence of ACLF and AKI was strongly associated with mortality. 28-day transplant-free mortality and 90-day transplant-free mortality of patients with ACLF (32% and 49.8%, respectively) were significantly higher with respect to those of patients without ACLF (6.2% and 16.4%, respectively; both p<0.001). Corresponding values in patients with and without AKI were 46% and 59%, and 12% and 25.6%, respectively (p<0.0001 for both). ACLF classification was more accurate than AKI classification in predicting 90-day mortality (area under the receiving operating characteristic curve=0.72 vs 0.62; p<0.0001) in the whole series of patients. Moreover, assessment of ACLF classification at 48 h had significantly better prognostic accuracy compared with that of both AKI classification and ACLF classification at enrolment. Conclusions: ACLF stratification is more accurate than AKI stratification in the prediction of short-term mortality in patients with acute decompensation of cirrhosis.